CORRESPONDÊNCIA ENTRE A PERCEPÇÃO MATERNA E O ESTADO NUTRICIONAL DE ESCOLARES - Luana da Silva Baptista Arpini; André Fiorin Arpini; Gláucia Figueiredo Justo; Geovane Carlos Barbosa; Luciane Bresciani Salaroli; Maria del Carmen Bisi Molina (Universidade do Estado do Rio de Janeiro, 2015)
Introduction: Maternal perception (MP) of the nutritional statusof the child (NS), when mismatched with the diagnosis, can leadto nutritional disorders. Objective: To evaluate the correlationbetween maternal perception and the nutritional status ofschoolchildren as well as the associated factors. Methods: Sampleconsisted of 518 schoolchildren aged 7-10 years. Anthropometricdata were collected for diagnosing nutritional status using thebody mass index (BMI) and socioeconomic data, and maternalperception by interviewing the mothers. Prevalence-adjustedKappa (k) to verify the correspondence between MP and NS,chi-square and Fisher's exact tests to determine differences inproportions, and multinomial logistic regression to adjust forassociated variables, were applied. Results: Highest and lowestcorrespondences between the MP and NS were found for thinnessand obesity. Male schoolchildren and those whose mothersare concerned with weight are more likely to be perceived as"underweight". Conclusion: Substantial agreement betweennutritional status and maternal perception was found. DOI: 10.12957/demetra.2015.15116